Outcome-Based Performance Management in the Public Sector (System Dynamics for Performance Management & Governance,, 2018)
This book highlights the use of an outcome-oriented view of performance to frame and assess the desirability of the effects produced by adopted policies, so to allow governments not only to consider effects in the short, but also the long run. Furthermore, it does not only focus on policy from the perspective of a single unit or institution, but also under an inter-institutional viewpoint. This book features theoretical and empirical research on how public organizations have evolved their performance management systems toward outcome measures that may allow one to better deal with wicked problems. Today, 'wicked problems' characterize most of governmental planning involving social issues. These are complex policy problems, underlying high risk and uncertainty, and a high interdependency among variables affecting them. Such problems cannot be clustered within the boundaries of a single organization, or referred to specific administrative levels or ministries. They are characterized by dynamic complexity, involving multi-level, multi-actor and multi-sectoral challenges. In the last decade, a number of countries have started to develop new approaches that may enable to improve cohesion, to effectively deal with wicked problems. The chapters in this book showcase these approaches, which encourage the adoption of more flexible and pervasive governmental systems to overcome such complex problems. Outcome-Based Performance Management in the Public Sector is divided into five parts. Part 1 aims at shedding light on problems and issues implied in the design and implementation of "outcome-based" performance management systems in the public sector. Then Part 2 illustrates the experiences, problems, and evolving trends in three different countries (Scotland, USA, and Italy) towards the adoption of outcome-based performance management systems in the public sector. Such analyses are conducted at both the national and local government levels. The third part of the book frames how outcome-based performance management can enhance public governance and inter-institutional coordination. Part 4 deals with the illustration of challenges and results from different public sector domains. Finally the book concludes in Part 5 as it examines innovative methods and tools that may support decision makers in dealing with the challenges of outcome-based performance management in the public sector. Though the book is specifically focused on a research target, it will also be useful to practitioners and master students in public administration . .